2016
DOI: 10.1097/ruq.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

Application of Thyroid Imaging Reporting and Data System in the Ultrasound Assessment of Thyroid Nodules According to Physician Experience

Abstract: In conclusion, the diagnostic performance of the stratification of malignancy risk according to TIRADS categories was comparable between the experienced and less experienced physician groups. The application of TIRADS is reproducible, and it was easy to predict the probability of thyroid malignancy in both the experienced and less experienced physician groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…was the easiest method in the clinical application and was used in our study. The high sensitivity and NPV (99.6% and 96.6%) obtained in the current study were consistent with the previous studies (sensitivity, 97.4–99.1% and NPV, 98.1–99.1%) 23 , 27 , 28 . In addition, a recent report used the TI-RADS proposed by Horvath et al .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…was the easiest method in the clinical application and was used in our study. The high sensitivity and NPV (99.6% and 96.6%) obtained in the current study were consistent with the previous studies (sensitivity, 97.4–99.1% and NPV, 98.1–99.1%) 23 , 27 , 28 . In addition, a recent report used the TI-RADS proposed by Horvath et al .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, some other US signs, such as halo sign, nodule size and vascularity, which were not considered by Ko et al . 23 , were proposed as significant predictors in diagnosing malignant TNs in other previous studies 24 26 . Therefore, these US features should be considered when developing a scoring system to predict malignancy in indeterminate nodules.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, intra- and interobserver variabilities in interpreting the US results exist. However, previous published data from our institution revealed more than a moderate degree of agreement in US assessment of thyroid nodules among experienced radiologists [38] and other studies have also shown that the diagnostic performances of malignant stratification using TIRADS categories are comparable regardless of the performer’s level of experience [39, 40]. These results support our opinion that any bias due to having 10 different US operators participate in the present study did not significantly affect our study results nor their interpretation.…”
Section: Discussionmentioning
confidence: 87%